1996
DOI: 10.1248/bpb.19.1109
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Anandamide Amidase Activity in Mouse Brain Microsomes by Cannabinoids.

Abstract: Mouse brain microsomes contain an amidase that catalyzes the hydrolysis of N-arachidonylethanolamide to arachidonic acid and ethanolamine. The enzymatic activity is dependent on the protein concentration of the microsomes and observed over a wide range of pH, 7.4 to 9.5. Kinetic analysis indicated that K(m) (microM) and Vmax (nmol/min/mg protein) were 17.7 +/- 4.1 and 1.81 +/- 0.32, respectively. Cannabidiol (CBD), cannabinol (CBN) and delta 9-tetrahydrocannabinol (delta 9-THC) significantly inhibited the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 0 publications
3
69
1
2
Order By: Relevance
“…with an IC 50 420 mM). The activity of CBD in this study was higher than that previously reported for anandamide hydrolysis by mouse brain (Watanabe et al, 1996;, where however only a very high concentration of the compound (160 mM) was used.…”
Section: Effect Of Cbd Analogues On Fatty Acid Amide Hydrolasecontrasting
confidence: 78%
See 2 more Smart Citations
“…with an IC 50 420 mM). The activity of CBD in this study was higher than that previously reported for anandamide hydrolysis by mouse brain (Watanabe et al, 1996;, where however only a very high concentration of the compound (160 mM) was used.…”
Section: Effect Of Cbd Analogues On Fatty Acid Amide Hydrolasecontrasting
confidence: 78%
“…As it was found to inhibit the reuptake and hydrolysis of AEA in vitro (Rakhshan et al, 2000;Watanabe et al, 1996), it is possible that CBD acts in part by interfering with AEA inactivation, thereby enhancing the putative tonic inhibitory action of AEA on in¯ammation. The fact that the pharmacological actions of CBD are not in¯uenced by CB 1 /CB 2 receptor antagonists should not be taken as evidence against this hypothesis, since it is now established that AEA also acts upon non-cannabinoid receptor targets, including VR1 receptors and TASK-1 K + channels (Zygmunt et al, 1999;Maingret et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBD has been implicated in modulating the metabolism of the endocannabinoid, arachidonoylethanolamide (AEA; also 'anandamide') in vitro [118,119]. Transporter proteins are involved in regulating AEA-mediated cellular signaling and have also been reported to be targets for CBD [19,71].…”
Section: Anandamide Transportersmentioning
confidence: 99%
“…CBD has minimal affinity for CB1 receptors (Pertwee, 1997b), although it appears to interact with the endocannabinoid system via fatty acid amide hydrolase (Watanabe et al, 1996) or through the putative anandamide membrane transporter (Bisogno et al, 2001). CBD also has been found to have agonist activity at TRPV1 (Bisogno et al, 2001) and at 5-HT1A receptors (Russo et al, 2005).…”
Section: Putative Mechanisms For Thc and Cbd Interactionsmentioning
confidence: 99%